Few-layer tin–antimony nanosheets: a novel 2D alloy for superior lithium storage. Issue 27 (15th March 2019) - Gu, Jianan; Ma, Jingui; Du, Zhiguo; Zhang, Chao; Yang, Shubin
Abstract : A novel 2D alloy, free-standing few-layer SnSb nanosheets, is fabricated via a liquid-phase exfoliation approach. Abstract : A novel 2D alloy, free-standing few-layer SnSb nanosheets, is fabricated via a liquid-phase exfoliation approach. The resultant few-layer SnSb possesses ultrathin features (1–4 nm), large aspect ratio, largely exposed surfaces and a precise stoichiometric ratio between Sn and Sb (1 : 1). These few-layer SnSb nanosheets are systematically investigated for lithium storage, and exhibit a high reversible capacity of 694 mA h g −1, high rate capability and good cycling performance, as we expected.